ENHANCING EMPLOYABILITY: STRATEGIES FOR IMPROVING JOB SEARCH SKILLS AMONG TVET ESL GRADUATES - Nor Rulmaisura Mohamad; Nurul Ajleaa Abdul Rahman; Goh Ying Soon; Siti Zuhra Abu Bakar (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study investigates the employment barriers faced by graduates from Technical and Vocational Education and Training (TVET) programs, with a focus on the challenges of creating compelling cover letters and resumes and excelling in job interviews. Employing a comprehensive mixed-methods approach that combines quantitative surveys and qualitative interviews, this research explores the experiences of TVET graduates to understand the complexities of job-seeking challenges. The findings indicate that many graduates struggle with presenting their skills and experiences effectively in written applications and experience significant anxiety and lack of preparation during interviews. These issues are exacerbated by language proficiency and self-confidence challenges, highlighting the need for targeted support and training. The paper offers practical recommendations for educators, career counsellors, and policymakers to integrate specialized training modules and workshops to enhance TVET graduates’ job search skills. The goal is to equip these graduates with the tools needed to succeed in a competitive job market.